Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine whether the given expressions are trigonometric identities, we need to simplify each expression step-by-step and check if they hold true for all values of \(x\).
### Expression A
[tex]\[ (\sin x + \cos x)^2 = 1 + \sin 2x \][/tex]
1. Expand the left-hand side:
[tex]\[ (\sin x + \cos x)^2 = \sin^2 x + 2 \sin x \cos x + \cos^2 x \][/tex]
2. Use the Pythagorean identity \(\sin^2 x + \cos^2 x = 1\):
[tex]\[ 1 + 2 \sin x \cos x \][/tex]
3. Recognize that \(2 \sin x \cos x = \sin 2x\):
[tex]\[ 1 + \sin 2x \][/tex]
The left-hand side simplifies exactly to the right-hand side. Therefore, this is an identity.
### Expression B
[tex]\[ \frac{\sin 3x - \sin x}{\cos 3x + \cos x} = \tan x \][/tex]
1. Use the sum-to-product identities for the numerator and denominator.
[tex]\[ \sin 3x - \sin x = 2 \cos \left(\frac{3x + x}{2}\right) \sin \left(\frac{3x - x}{2}\right) = 2 \cos(2x) \sin x \][/tex]
2. Similarly, for the denominator, use the sum-to-product identities:
[tex]\[ \cos 3x + \cos x = 2 \cos \left(\frac{3x + x}{2}\right) \cos \left(\frac{3x - x}{2}\right) = 2 \cos(2x) \cos x \][/tex]
3. Substituting these into the given expression:
[tex]\[ \frac{2 \cos(2x) \sin x}{2 \cos(2x) \cos x} = \frac{\sin x}{\cos x} = \tan x \][/tex]
This simplification confirms that the expression is an identity.
### Expression C
[tex]\[ \sin 6x = 2 \sin 3x \cos 3x \][/tex]
Using the double-angle formula \(\sin 2\theta = 2 \sin \theta \cos \theta\):
[tex]\[ \sin 6x = \sin (2 \cdot 3x) = 2 \sin 3x \cos 3x \][/tex]
This simplification confirms that the expression is an identity.
### Expression D
[tex]\[ \frac{\sin 3x}{\sin x \cos x} = 4 \cos x - \sec x \][/tex]
First, simplify the left-hand side:
[tex]\[ \frac{\sin 3x}{\sin x \cos x} \][/tex]
Using the triple angle identity for sine:
[tex]\[ \sin 3x = 3 \sin x - 4 \sin^3 x \][/tex]
Substitute back into the expression:
[tex]\[ \frac{3 \sin x - 4 \sin^3 x}{\sin x \cos x} = \frac{3 \sin x}{\sin x \cos x} - \frac{4 \sin^3 x}{\sin x \cos x} \][/tex]
[tex]\[ = \frac{3}{\cos x} - \frac{4 \sin^2 x}{\cos x} \][/tex]
Using \(\sin^2 x = 1 - \cos^2 x\):
[tex]\[ = \frac{3}{\cos x} - \frac{4 (1-\cos^2 x)}{\cos x} \][/tex]
[tex]\[ = \sec x - \frac{4 (1-\cos^2 x)}{\cos x} \][/tex]
[tex]\[ = \sec x - 4 \left(\frac{1}{\cos x} - \cos x \right) \][/tex]
[tex]\[ = \sec x - 4 \sec x + 4 \cos x \][/tex]
Simplify:
[tex]\[ \sec x - 4 \sec x + 4 \cos x = -3 \sec x + 4 \cos x \][/tex]
This does not match the right-hand side of the given expression \(4 \cos x - \sec x\).
Thus, the expressions that are identities are:
- Expression A
- Expression C
### Expression A
[tex]\[ (\sin x + \cos x)^2 = 1 + \sin 2x \][/tex]
1. Expand the left-hand side:
[tex]\[ (\sin x + \cos x)^2 = \sin^2 x + 2 \sin x \cos x + \cos^2 x \][/tex]
2. Use the Pythagorean identity \(\sin^2 x + \cos^2 x = 1\):
[tex]\[ 1 + 2 \sin x \cos x \][/tex]
3. Recognize that \(2 \sin x \cos x = \sin 2x\):
[tex]\[ 1 + \sin 2x \][/tex]
The left-hand side simplifies exactly to the right-hand side. Therefore, this is an identity.
### Expression B
[tex]\[ \frac{\sin 3x - \sin x}{\cos 3x + \cos x} = \tan x \][/tex]
1. Use the sum-to-product identities for the numerator and denominator.
[tex]\[ \sin 3x - \sin x = 2 \cos \left(\frac{3x + x}{2}\right) \sin \left(\frac{3x - x}{2}\right) = 2 \cos(2x) \sin x \][/tex]
2. Similarly, for the denominator, use the sum-to-product identities:
[tex]\[ \cos 3x + \cos x = 2 \cos \left(\frac{3x + x}{2}\right) \cos \left(\frac{3x - x}{2}\right) = 2 \cos(2x) \cos x \][/tex]
3. Substituting these into the given expression:
[tex]\[ \frac{2 \cos(2x) \sin x}{2 \cos(2x) \cos x} = \frac{\sin x}{\cos x} = \tan x \][/tex]
This simplification confirms that the expression is an identity.
### Expression C
[tex]\[ \sin 6x = 2 \sin 3x \cos 3x \][/tex]
Using the double-angle formula \(\sin 2\theta = 2 \sin \theta \cos \theta\):
[tex]\[ \sin 6x = \sin (2 \cdot 3x) = 2 \sin 3x \cos 3x \][/tex]
This simplification confirms that the expression is an identity.
### Expression D
[tex]\[ \frac{\sin 3x}{\sin x \cos x} = 4 \cos x - \sec x \][/tex]
First, simplify the left-hand side:
[tex]\[ \frac{\sin 3x}{\sin x \cos x} \][/tex]
Using the triple angle identity for sine:
[tex]\[ \sin 3x = 3 \sin x - 4 \sin^3 x \][/tex]
Substitute back into the expression:
[tex]\[ \frac{3 \sin x - 4 \sin^3 x}{\sin x \cos x} = \frac{3 \sin x}{\sin x \cos x} - \frac{4 \sin^3 x}{\sin x \cos x} \][/tex]
[tex]\[ = \frac{3}{\cos x} - \frac{4 \sin^2 x}{\cos x} \][/tex]
Using \(\sin^2 x = 1 - \cos^2 x\):
[tex]\[ = \frac{3}{\cos x} - \frac{4 (1-\cos^2 x)}{\cos x} \][/tex]
[tex]\[ = \sec x - \frac{4 (1-\cos^2 x)}{\cos x} \][/tex]
[tex]\[ = \sec x - 4 \left(\frac{1}{\cos x} - \cos x \right) \][/tex]
[tex]\[ = \sec x - 4 \sec x + 4 \cos x \][/tex]
Simplify:
[tex]\[ \sec x - 4 \sec x + 4 \cos x = -3 \sec x + 4 \cos x \][/tex]
This does not match the right-hand side of the given expression \(4 \cos x - \sec x\).
Thus, the expressions that are identities are:
- Expression A
- Expression C
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.